1982
DOI: 10.1212/wnl.32.5.503
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of (‐) deprenyl to amphetamine and methamphetamine may be responsible for deprenyl's therapeutic benefit

Abstract: The urinary excretion of some important phenylethylamines, catecholamines, their metabolites, amphetamine, and methamphetamine were measured in parkinsonian patients on Sinemet (L-dopa plus carbidopa, a peripheral dopadecarboxylase inhibitor) and depressed patients after chronic (-) deprenyl treatment. Deprenyl was efficiently metabolized to amphetamine and methamphetamine. It increased the excretion of phenylethylamine and of m- and p-tyramine, and reduced the output of norepinephrine metabolites, but failed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Celada and Artigas (1993) reported that the irreversible MAO-A inhibitor clorgyline, together with the irreversible MAO-B inhibitor selegiline, increased extracellular serotonin levels more than clorgyline alone did. Selegiline is partly metabolized to L-amphetamine (Karoum et al, 1982). Therefore, another mechanism other than MAO inhibition might explain the enhancement of serotonin increase by selegiline in their study.…”
Section: Discussionmentioning
confidence: 78%
“…Celada and Artigas (1993) reported that the irreversible MAO-A inhibitor clorgyline, together with the irreversible MAO-B inhibitor selegiline, increased extracellular serotonin levels more than clorgyline alone did. Selegiline is partly metabolized to L-amphetamine (Karoum et al, 1982). Therefore, another mechanism other than MAO inhibition might explain the enhancement of serotonin increase by selegiline in their study.…”
Section: Discussionmentioning
confidence: 78%
“…One explanation for the effect of L-deprenyl is that deprenyl is converted to L-amphetamine, and this in turn inhibits dopamine uptake via DAT or NET (Karoum et al, 1982;Tetrud and Langston, 1989;Okudo et al, 1992). However, all MAO inhibitors tested in the present study decreased the dopamine clearance rate.…”
Section: Processes Of Mpfc Dopamine Clearance In Vitromentioning
confidence: 99%
“…Hence MAO-A rather than MAO-B inhibition could cause increased dopamine levels with prolonged (-)-deprenyl treatment and might explain the apparent slowing found in clinical trials. ( -)-Deprenyl is mainly metabolized to (-)-desmethyldeprenyl, (-)-methamphetamine and (-)-amphetamine (Karoum et al, 1982). The (-)-enantiomers of amphetamine and methamphetamine have a 10 times weaker effect on attention than ( + )-methamphetamine and ( + )-amphetamine (Taylor and Snyder, 1974) so that concentrations of the (-)-enantiomers produced by a 10mg daily dose of (-)-deprenyl are considered too small to influence attention which could in turn account for improved cognitive performance in AD (Gerlach et al, 1992).…”
mentioning
confidence: 99%